2018
DOI: 10.1002/jbm.a.36335
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic cellular activity around onlaid octacalcium phosphate‐gelatin composite onto rat calvaria

Abstract: The activity and the distribution of osteogenic cells around octacalcium phosphate (OCP) granules combined with gelatin matrix (OCP/Gel) onlaid on rat calvaria were analyzed histomorphometrically and immunohistochemically during vertical bone augmentation under mechanical or nonmechanical environment until 8 weeks. OCP/Gel disk was placed in subperiosteal pocket on the calvaria with or without polytetrafluoroethylene (PTFE) support. The latter is a nonmechanical stress model to alleviate the mechanical stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
(61 reference statements)
1
1
0
Order By: Relevance
“…The effect of the gelatin matrix with OCP might have also accelerated the biodegradation of the OCP particles. 39 Studies showed that highly resorbable and osteoconductive biomaterials, such as OCP/Gel composite, have potential use in clinical practice, which is consistent with those of the present study. Further studies are necessary to investigate the relationship between the rapid biodegradability and bone regenerative capacity of the OCP/Gel composite.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of the gelatin matrix with OCP might have also accelerated the biodegradation of the OCP particles. 39 Studies showed that highly resorbable and osteoconductive biomaterials, such as OCP/Gel composite, have potential use in clinical practice, which is consistent with those of the present study. Further studies are necessary to investigate the relationship between the rapid biodegradability and bone regenerative capacity of the OCP/Gel composite.…”
Section: Discussionsupporting
confidence: 92%
“…For example, OCP granules were combined with gelatin and the prepared composites were spread on rat calvaria. Those composites were found to promote bone growth due to the balanced cellular activity of osteoblasts and osteoclasts [473]. There is also an excellent review on OCP/polymer biocomposites with a controlled hierarchical structure from the macro to the nanoscale [474].…”
Section: Biocomposites With Remaining Capomentioning
confidence: 99%